Peran Maqashid Syari’ah dalam Mewujudkan Keadilan, Kesejahteraan, dan Stabilitas Sistem Ekonomi Islam: Perspektif Umar Chapra - Risa Aprilida (Universitas Siliwangi); Yulfi Rohmatul Hasanah (Universitas Siliwangi); Dzakwan Afaf Muhammad (Universitas Siliwangi); M.Aditya Saputra (Universitas Siliwangi); Lina Marlina (Universitas Siliwangi); Ana Fauziyah Diyana (Universitas Siliwangi) (Universitas Muhammadiyah Lampung, 2026)
This study aims to analyze the role of Maqashid al-Shari’ah in realizing justice, welfare, and stability within the Islamic economic system from the perspective of Umar Chapra. Maqashid al-Shari’ah, as the fundamental objectives of Islamic law, emphasizes the protection of religion (hifz ad-din), life (hifz an-nafs), intellect (hifz al-‘aql), lineage (hifz an-nasl), and wealth (hifz al-mal), which substantively form the normative foundation for developing a just and balanced economic system. According to Umar Chapra, the Islamic economic system is not merely oriented toward material growth but also toward equitable wealth distribution, poverty alleviation, moral development, and socio-economic stability.This research employs a qualitative approach using a library research method by examining Umar Chapra’s major works and relevant literature on Maqashid al-Shari’ah and Islamic economics. The findings indicate that the implementation of Maqashid al-Shari’ah in fiscal, monetary, and Islamic financial policies can create a balance between economic efficiency and distributive justice. Principles such as the prohibition of riba (usury), the obligation of zakat, and the strengthening of the real sector play significant roles in maintaining economic stability and preventing structural crises. In conclusion, Umar Chapra’s perspective affirms that Maqashid al-Shari’ah serves as both a philosophical and operational framework in constructing a just, sustainable, and welfare-oriented Islamic economic system. This study is expected to contribute to the enrichment of Islamic economic scholarship and to serve as a reference for policy formulation based on Shari’ah values.